THE CAMELLIA TRIAL: SCIENTIFIC VALUE AND RECOMMENDS FOR PRACTITIONER - S. Y. Martsevich; N. P. Kutishenko; S. A. Shalnova; R. G. Oganov (Столичная издательская компания, 2016)
The CAMELLIA trial: scientific value and recommends for practitioner.